Genetics of Sudden Cardiac Death. Issue 12 (5th June 2015) - Bezzina, Connie R.; Lahrouchi, Najim; Priori, Silvia G.
<x xml:space="preserve">Abstract</x> Sudden cardiac death occurs in a broad spectrum of cardiac pathologies and is an important cause of mortality in the general population. Genetic studies conducted during the past 20 years have markedly illuminated the genetic basis of the inherited cardiac disorders associated with sudden cardiac death. Here, we review the genetic basis of sudden cardiac death with a focus on the current knowledge on the genetics of the primary electric disorders caused primarily by mutations in genes encoding ion channels, and the cardiomyopathies, which have been attributed to mutations in genes encoding a broader category of proteins, including those of the sarcomere, the cytoskeleton, and desmosomes. We discuss the challenges currently faced in unraveling genetic factors that predispose to sudden cardiac death in the setting of sequela of coronary artery disease and present the genome-wide association studies conducted in recent years on electrocardiographic parameters, highlighting their potential in uncovering new biological insights into cardiac electric function.